(untitled) (MIST International Journal of Science and Technology, 2021)
Plume collection from cooling towers can be a reliable solution to the water scarcity problem faced in many regions around the world. Meshes are one of the most proposed collectors in this regard that rely upon inertial collision for droplet capture and are inherently limited by aerodynamics. This study quantifies the effect of electrical forces on water collection from the plume of an Induced Draft Counter Flow (IDCF) Cooling Tower by introducing sets of copper tubes at the exit of the tower. The imparting of net charge to the exhaust plume by instigating space charge directs the vapor towards the inside wall of copper tube forming water droplets. This arrangement instead of a mesh or net system, creates a lesser obstruction to flow. Fabrication of fill/packing with a corrugated wave pattern using PVC plastic demonstrates satisfactory cooling performance of the tower. An optimized L/G ratio is found to exist for maximum collection efficiency of water from plume at definite entering fluid temperatures by investigating with the entering warm water temperatures at 40°C, 45°C and 50°C while the dry bulb temperature of air ranges from 23.5°C to 30.1°C. The electricity consumption for this arrangement fluctuates from 2.78 kWh/m to 5.13 kWh/m for two L/G ratios (23.5 and 28.3). Where maximum collection percentage occurs at two different entering fluid temperatures, the power expended is below the minimum used for typical desalination plants. MIJST, Vol. 9(1), June 2020: 1-9